Cover Picture: Chameleon Metals: Autonomous Nano‐Texturing and Composition Inversion on Liquid Metals Surfaces (Angew. Chem. Int. Ed. 1/2020). Issue 1 (6th December 2019) - Martin, Andrew; Kiarie, Winnie; Chang, Boyce; Thuo, Martin
Abstract : Chameleon Metals . Metal passivating oxide layers are complex pseudo‐equilibrium systems with a plethora of undiscovered features. In their Research Article on page 352, M. Thuo et al. exploit the complexity of such a thin oxide layer to engineer surface design and structure, resulting in the formation of compositionally inverted surface features and nanoscale fractal‐like designs.